2020
DOI: 10.1590/0034-7167-2019-0425
|View full text |Cite
|
Sign up to set email alerts
|

Validating a Nursing Assessment instrument in a Pediatric Intensive Care Unit

Abstract: Objective: To develop and validate a Nursing History instrument for a Pediatric Intensive Care Unit, based on the Theory of Basic Human Needs. Methods: Methodological study, developed between October 2018 and April 2019, based on the establishment of a theoretical-conceptual structure; construction of items and of the response scale; selection and organization of items; structuring the instrument; expert opinion; and content and appearance validation. Results: The instrument was organized in three sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
1
0
4
Order By: Relevance
“…As Studies ( 18 , 19 , 20 ) have shown that “lack of time” can be considered a limiting condition to the implementation of the Nursing Process, others have shown that the Nursing Process favors the optimization of time, the sharing of knowledge and the implementation of a plan of goals previously induced by the team leader ( 21 , 22 ) . From this perspective, it can be seen that the Nursing Process requires greater theoretical and methodological depth on the part of local leaders, but also on the part of the nursing teams, in order for it to be seen as elementary and primordial when it comes to providing unique and multidimensional nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…As Studies ( 18 , 19 , 20 ) have shown that “lack of time” can be considered a limiting condition to the implementation of the Nursing Process, others have shown that the Nursing Process favors the optimization of time, the sharing of knowledge and the implementation of a plan of goals previously induced by the team leader ( 21 , 22 ) . From this perspective, it can be seen that the Nursing Process requires greater theoretical and methodological depth on the part of local leaders, but also on the part of the nursing teams, in order for it to be seen as elementary and primordial when it comes to providing unique and multidimensional nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto Estudos (18)(19)(20) demonstraram que a "falta de tempo" pode ser considerada condição limitadora à efetivação do Processo de Enfermagem, outros evidenciam que o Processo de Enfermagem favorece a otimização do tempo, o compartilhamento de saberes e a efetivação de um plano de metas previamente induzidos pelo líder da equipe (21)(22) . Percebe-se, sob esse enfoque, que o Processo de Enfermagem requer maior 8 de Percepção dos enfermeiros sobre o processo de enfermagem e sua relação com a liderança Bär KA, Lima BS, Martelle GM, Silva SC, Santos MR, Costenaro RGS.…”
Section: Discussionunclassified
“…A necessidade de hidratação, regulação hídrica e eletrolítica se apresentou como fator de influência forte, deixando clara a evidência de que as ações de caráter clínico de enfermagem, no histórico, são pertinentes no que diz respeito à detecção do estado inicial de hidratação da criança, mensuração do risco quanto à perda hídrica e à demanda de reposição de substâncias hidroeletrolíticas, tendo em vista a depreciação do quantitativo de eletrólitos e líquidos a cada afecção detectada durante a hospitalização que leva ao estabelecimento do quadro hídrico prejudicado [18]. Observa-se que, tanto na Figura (2a) como em (2b), a necessidade de Eliminação se distingue das demais, fato já verificado na Figura 1.…”
Section: Discussionunclassified
“…No que concerne à criança, autores demonstram a evidência de que as alterações clínicas podem ser mensuradas conforme estratificação de valores e a predição de tomadas de decisão sob julgamentos frente à aplicabilidade do uso de ferramentas durante a assistência de enfermagem, levando a melhorias no cuidado e precisão na medida do atributo o qual o instrumento propõe medir [18,19].…”
Section: Discussionunclassified